2021
DOI: 10.1111/tpj.15364
|View full text |Cite
|
Sign up to set email alerts
|

A forward genetics approach integrating genome‐wide association study and expression quantitative trait locus mapping to dissect leaf development in maize (Zea mays)

Abstract: SUMMARY The characterization of the genetic basis of maize (Zea mays) leaf development may support breeding efforts to obtain plants with higher vigor and productivity. In this study, a mapping panel of 197 biparental and multiparental maize recombinant inbred lines (RILs) was analyzed for multiple leaf traits at the seedling stage. RNA sequencing was used to estimate the transcription levels of 29 573 gene models in RILs and to derive 373 769 single nucleotide polymorphisms (SNPs), and a forward genetics appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 108 publications
(243 reference statements)
0
20
0
Order By: Relevance
“…SNPs are particularly useful for performing genome-wide association studies (GWAS) which can identify QTL and increase the resolution of QTL mapping ( Hu et al , 2017 ; Frascaroli and Revilla, 2019 ; Li et al , 2021 ). Genetic mapping performed using SNPs can also be used for marker-assisted selection and to identify candidate genes ( Miculan et al , 2021 ; Waqas et al , 2021 ). Once identified, candidate genes relating to physiological traits of interest may be classified according to functional characteristics using Gene Ontology (GO) terms; GO term annotations are now available for all of the protein-coding genes in maize ( Wimalanathan et al , 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…SNPs are particularly useful for performing genome-wide association studies (GWAS) which can identify QTL and increase the resolution of QTL mapping ( Hu et al , 2017 ; Frascaroli and Revilla, 2019 ; Li et al , 2021 ). Genetic mapping performed using SNPs can also be used for marker-assisted selection and to identify candidate genes ( Miculan et al , 2021 ; Waqas et al , 2021 ). Once identified, candidate genes relating to physiological traits of interest may be classified according to functional characteristics using Gene Ontology (GO) terms; GO term annotations are now available for all of the protein-coding genes in maize ( Wimalanathan et al , 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The found genomic regions controlling gene expression are referred to as expression-QTLs (eQTLs). Previous studies have reported that distant or trans-eQTLs may explain a higher proportion of expression variance than local (at the same locus as the structural gene) or cis -eQTLs ( Liu et al, 2017 ; Carrasco-Valenzuela et al, 2019 ; Fauteux et al, 2019 ; Miculan et al, 2021 ). Hotspots of trans-eQTL may act as key regulators of phenotypes, whereas cis -eQTLs display local gene expression regulation, with co-regulated gene clusters ( Wang et al, 2018 ; Miculan et al, 2021 ).…”
Section: Introductionmentioning
confidence: 94%
“…Previous studies have reported that distant or trans-eQTLs may explain a higher proportion of expression variance than local (at the same locus as the structural gene) or cis -eQTLs ( Liu et al, 2017 ; Carrasco-Valenzuela et al, 2019 ; Fauteux et al, 2019 ; Miculan et al, 2021 ). Hotspots of trans-eQTL may act as key regulators of phenotypes, whereas cis -eQTLs display local gene expression regulation, with co-regulated gene clusters ( Wang et al, 2018 ; Miculan et al, 2021 ). Several studies have been using a hybrid approach (pQTL and eQTL analyses) to better understand the gene networks underlying traits of interest in plants ( Lima et al, 2018 ; Carrasco-Valenzuela et al, 2019 ; Fauteux et al, 2019 ; Miculan et al, 2021 ).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Although these marker-assisted breeding technologies have a major impact on the accuracy and speed of crop breeding, the genes underlying the QTLs are in many cases unknown. In recent years, technological advances have combined GWAS with molecular -omics phenotypes that go beyond the genomic information, so that molecular networks start to emerge in molecular breeding (Baute et al, 2015; Baute et al, 2016; Xiao et al, 2016; Miculan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%